Apa yang Mendorong Kepuasan Finansial Indonesia di Masa Wabah Covid-19? - Gesti Memarista; Visi Saujaningati Kristyanto; Natalia Kristina (Universitas Kristen Maranatha, 2022)
Financial satisfaction has changed since the Covid-19 pandemic since many people experience health problems, lose their jobs, until psychological disorders. This study aims to determine the factors driving income earners' financial satisfaction before and during the Covid-19 outbreak in Indonesia. The variables studied are religiosity, ethnicity, and health level related to financial activities. This research method uses a quantitative approach to estimate the factors that influence financial satisfaction using multiple linear regression and comparison tests between financial satisfaction before and during the Covid-19 outbreak. There are 159 respondents in this study. The research result shows that religiosity and the ethnic had no significant effect on financial satisfaction before and during the Covid-19 outbreak. Yet, the health level significantly impacted financial satisfaction before and during the Covid-19 outbreak. Health level is an essential factor so that a person can work very well to generate income and obtain financial satisfaction. The respondents’ financial satisfaction before and during the Covid-19 is significantly different. Respondents also have more financial anxiety during the Covid-19 outbreak. The research implication is that the Indonesian people must consider financial planning that suits with financial conditions. Due to the more suitable financial planning, it will increase Indonesian financial satisfaction even during the Covid-19 outbreak.